Changes in tramadol enantioselective pharmacokinetics and metabolism in rats with experimental diabetes treated or not with insulin - Godoy, Ana Leonor Pardo Campos (2019)
This study aimed to investigate the impact of diabetes treated or not with insulin in the enantioselective pharmacokinetics of tramadol (trans-T) and its phase 1 metabolites O-desmethyltramadol (M1) and N-desmethyltramadol (M2). The CYP2D inhibitor quinidine was used to simulate the poor metabolizer phenotype. Male Wistar rats were divided into groups: control, quinidine (80-mg/kg quinidine intraperitoneally 4 h before trans-T), diabetic (45-mg/kg STZ i.v.), diabetes + insulin (2 IU/day insulin for 12 days), diabetes + quinidine and diabetes + insulin + quinidine. All animals (n = 6, per sampling time) received 20-mg/kg trans-T orally. The kinetic disposition of trans-T is enantioselective in control with higher AUC of (+)-trans-T than for its antipode. Quinidine reduced AUC ratios (+)-M1/(+)-trans-T and (−)-M1/(−)-trans-T compared to Control. Diabetes increased plasma concentrations of (+)-trans-T, (−)-trans-T, (+)-M1, (−)-M1 and (+)-M2 compared to control, but without changing AUC ratios M1/trans-T or M2/trans-T. Insulin reverted the effect of diabetes only for (−)-trans-T. The simulated diabetes in CYP2D poor metabolizers showed reduced metabolic ratios for M1 enantiomers. In conclusion, diabetes resulted in higher plasma concentrations of the active (+)-trans-T, (−)-trans-T and (+)-M1, suggesting down-regulation of CYP3A and OCT1. The glycemic control of diabetes by insulin reduces partially the impact of diabetes on trans-T pharmacokinetics.